Incidence of Refeeding Syndrome in Critically Ill Children With Nutritional Support - Blanc, Stéphanie; Vasileva, Tajnja; Tume, Lyvonne N.; Baudin, Florent; Chessel Ford, Carole; Chaparro Jotterand, Corinne; Valla, Frederic V. (Frontiers in Pediatrics, 2022)
Introduction : Early enteral nutrition is recommended for critically ill children, potentially exposing those who are malnourished to the risk of refeeding syndrome. However, data on its incidence is lacking, and the heterogeneity of diagnostic criteria and frequent electrolyte disorders in this population make its diagnosis complex. In 2020, the American Society for Parenteral and Enteral Nutrition (ASPEN) developed consensus recommendations for identifying patients at risk for refeeding syndrome. The aim of this study was to determine the incidence of refeeding syndrome according to the ASPEN definition in critically ill children on nutritional support. Materials and methods : A single-center restrospective cohort study was conducted in a tertiary pediatric intensive care unit in France. According to the criteria established by the ASPEN, children were considered at risk of developing refeeding syndrome if they were undernourished. Those who developed one significant electrolyte disorder (decrease ≥10% of phosphorus, potassium, and/or magnesium) within the first five days of nutritional support, combined with a significant increase in energy intake, were considered to have probable refeeding syndrome. Results : A total of 1261 children were included in the study, with 199 children (15.8%) classified as undernourished, who were at risk of refeeding syndrome. Of these, 93 children were identified as having probable refeeding syndrome, giving an overall incidence of 7.4%. The incidence rate among at-risk children was 46.7%. Most patients (58.1%) were classified as having severe refeeding syndrome. Conclusion: Refeeding syndrome remains difficult to diagnose in critically ill children, due to frequent confounding factors impacting electrolyte plasma levels. These findings suggest that refeeding syndrome incidence may be high in undernourished children, and that refeeding syndromes can be severe. Further prospective studies using the ASPEN definition and risk criteria are required.